Cross-reactive human B cell and T cell epitopes between influenza A and B viruses - Terajima, Masanori; Babon, Jenny Aurielle B; Co, Mary Dawn T; Ennis, Francis A (Virology journal, 2013)
Influenza A and B viruses form different genera, which were originally distinguished by antigenic differences in their nucleoproteins and matrix 1 proteins. Cross-protection between these two genera has not been observed in animal experiments, which is consistent with the low homology in viral proteins common to both viruses except for one of three polymerase proteins, polymerase basic 1 (PB1). Recently, however, antibody and CD4⁺T cell epitopes conserved between the two genera were identified in humans. A protective antibody epitope was located in the stalk region of the surface glycoprotein, hemagglutinin, and a CD4⁺T cell epitope was located in the fusion peptide of the hemagglutinin. The fusion peptide was also found to contain antibody epitopes in humans and animals. A short stretch of well-conserved peptide was also identified in the other surface glycoprotein, neuraminidase, and antibodies binding to this peptide were generated by peptide immunization in rabbits. Although PB1, the only protein which has relatively high overall sequence homology between influenza A and B viruses, is not considered an immunodominant protein in the T cell responses to influenza A virus infection, amino acid sequence comparisons show that a considerable number of previously identified T cell epitopes in the PB1 of influenza A viruses are conserved in the PB1 of influenza B viruses. These data indicate that B and T cell cross-reactivity exists between influenza A and B viruses, which may have modulatory effects on the disease process and recovery. Although the antibody titers and the specific T cell frequencies induced by natural infection or standard vaccination may not be high enough to provide cross protection in humans, it might be possible to develop immunization strategies to induce these cross-reactive responses more efficiently.